2017
DOI: 10.1017/s0950268817002606
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HEV-specific antibodies in four non-human primate species, including great apes, from different zoos in Germany

Abstract: The hepatitis E virus (HEV) has been described in humans and various animal species in different regions of the world. However, the knowledge on natural HEV infection in non-human primates and the corresponding risk of zoonotic transmission is scarce. To determine whether primates in captivity are affected by HEV infection, we investigated 259 individual sera of clinically healthy non-human primates of 14 species from nine German zoos. Using a commercial double-antigen-sandwich ELISA and a commercial IgG ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Five of the 33 species tested presented at least one animal with anti‐HEV antibodies. The seropositivity detected in our study (4.4%) was in accordance with that found in NHPs in zoos in Italy (4.6%; 4/86) and Germany (3.9%; 10/259) (Melegari et al, ; Spahr, Knauf‐Witzens, Dähnert, et al, ). In contrast, previous studies failed to detect anti‐HEV antibodies in NHPs in zoos from China (0/2) and Korea (0/1) (Song et al, ; Zhang et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Five of the 33 species tested presented at least one animal with anti‐HEV antibodies. The seropositivity detected in our study (4.4%) was in accordance with that found in NHPs in zoos in Italy (4.6%; 4/86) and Germany (3.9%; 10/259) (Melegari et al, ; Spahr, Knauf‐Witzens, Dähnert, et al, ). In contrast, previous studies failed to detect anti‐HEV antibodies in NHPs in zoos from China (0/2) and Korea (0/1) (Song et al, ; Zhang et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, since there is a direct relationship between volume of food ingested and size of animal, the probability of HEV infection could also be proportionally higher. Ingestion of contaminated water or meat products is considered the main route of HEV transmission in humans (Pavio et al, ) and probably also in NHPs (Spahr, Knauf‐Witzens, Dähnert, et al, ). However, since the diet of these species is mainly herbivore and the virus has also been detected in fruit and vegetables (Kokkinos et al, ; Terio et al, ), they should be considered possible sources of infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study also showed the presence of anti-HEV IgG antibodies among gorilla and drill in Germany. 11 Some studies have shown the presence of anti-HEV IgG antibodies in other species of non-human primates, including the Japanese monkeys, rhesus monkeys, cynomolgus monkeys, Taiwanese monkey and white-naped mangabey. 9,10,12 Meanwhile three NHP in this study had IgM markers indicative of recent HEV infection, that is, chimpanzee, olive baboon and agile mangabey.…”
Section: Discussionmentioning
confidence: 99%